Personal Experiences in Post-Shoah Greece: The Case of Isaak Menahem Rousso - Droumpouki, Anna Maria (Historein, 2019)
In December 1971, twelve years after his first letter to the West German government, 73-year-old Isaak Menahem Rousso exclaimed: “I ask you, what did I do to you for you to destroy my wealth, my shops? You killed my parents, and now you want to pay me a pittance”? The article focuses on the individual struggle of a Jewish survivor to receive compensation from the Federal Republic of Germany, as can be traced in the personal archive of Isaak Menahem Rousso. It examines the numerous letters he sent to German officials during the 1960s and 1970s, documents and contextualises his feelings of despair, fear and anger, and elucidates upon them. These feelings are typical for the Greek Jewish survivors that sought compensation. Survivors complained that the claims evaluation process constituted an unpleasant and inhumane experience. Many found it very difficult to return to the past and remember their suffering, as some of them already felt guilt or shame for having survived, not to mention the pain that reliving these traumatic experiences incurred. Many victims suffered from post-traumatic disorders and it was not easy to revive these experiences. Through Isaak Menahems’ story, I want to explore the survivors’ feelings in their search for recognition and compensation.